AN ASSESSMENT OF THEATRE EFFICIENCY IN AN AFRICAN TEACHING HOSPITAL - Babayo UD; Bello US (Ntec Specialist, 2017)
Background: Operating theatre or operating room (OR in the US) is a designed facility where surgical operations take place. With an estimated 234 million operations performed yearly, and about half of its complications, of avoidable events, theatre efficiency is essential. Simple data collection from theatre users can serve as a platform for audit, research and an instrument for change that can reduce rate of cancellations, cost and waiting time. As no consensus exist on ways of evaluating operating theatre management decision, this article serves as a bridge. Objectives: This study will serve as a platform for theatre reforms with the aim of improving efficiency; it is also an instrument for surgical audit. Methodology: Structured questionnaires containing 20 questions with each comprising 5 optional response: Strongly agreed, agreed, neutral, disagree, strongly disagree were distributed. We investigated the efficiency of the University of Maiduguri Teaching Hospital (UMTH) theatres as perceived by users. Results: The results reveals 80.59% agree that operation list do not start on time and 56.8 % suggest that surgeons don't come on time, but disagreement that the theatre room is conducive and comfortable has the highest commonality of purpose at 92.53%. Conclusion: Our study findings suggest that general disagreements outweigh the agreement in most variables studied. This study reveals a long turnaround of patient (68.18%) who also stays long at the reception (69.64%). There is a general disagreement on reliable quality equipment, comfortable rest room, comfortable and adequate support for day care with 70.14%, 74.24%, 68.18%, and 72.72% respectively